Winter climate change and the poleward range expansion of a tropical invasive tree (Brazilian pepper—Schinus terebinthifolius). (27th October 2019) - Osland, Michael J.; Feher, Laura C.
Abstract: Winter climate change is expected to lead to the tropicalization of temperate ecosystems, where tropical species expand poleward in response to a decrease in the intensity and duration of winter temperature extremes (i.e., freeze events). In the southeastern United States, freezing temperatures control the northern range limits of many invasive nonnative species. Here, we examine the influence of freezing temperatures and winter climate change on the northern range limits of an invasive nonnative tree— Schinus terebinthifolius (Brazilian pepper). Since introduction in the 1800s, Brazilian pepper has invaded ecosystems throughout south and central Florida to become the state's most widespread nonnative plant species. Although Brazilian pepper is sensitive to freezing temperatures, temperature controls on its northern distribution have not been adequately quantified. We used temperature and plant occurrence data to quantify the sensitivity of Brazilian pepper to freezing temperatures. Then, we examined the potential for range expansion under three alternative future climate scenarios (+2°C, +4°C, and +6°C). Our analyses identify a strong nonlinear sigmoidal relationship between minimum temperature and Brazilian pepper presence, with a discrete threshold temperature occurring near −11°C. Our future scenario analyses indicate that, in response to warming winter temperatures, Brazilian pepper is expected to expand northward and transform ecosystems in north Florida and across much of the Gulf of Mexico and south Atlantic coasts of the United States. These results underscore the importance of early detection and rapid response efforts to identify and manage the northward invasion of Brazilian pepper in response to climate change. Looking more broadly, our work highlights the need to anticipate and prepare for the tropicalization of temperate ecosystems by tropical invasive species. Abstract : Winter climate change is expected to lead to the tropicalization of temperate ecosystems, where tropical species expand poleward in response to a decrease in the intensity and duration of winter temperature extremes (i.e., freeze events). In the southeastern United States, freezing temperatures control the northern range limits of many invasive nonnative species. Here, we examine the influence of freezing temperatures and winter climate change on the northern range limits of an invasive nonnative tree— Schinus terebinthifolius (Brazilian pepper).